2010
DOI: 10.1002/qua.22901
|View full text |Cite
|
Sign up to set email alerts
|

Steric and electronic effects on the heterolytic H2‐splitting by phosphine‐boranes R3B/PR′3(R = C6F5, Ph; R′ = C6H2Me3,tBu, Ph, C6F5, Me, H): A computational study

Abstract: The steric and electronic effects exerted by the substituents R/R 0 on the heterolytic H 2 -splitting by phosphine-boranes R 3 B/PR 0 3 [R ¼ C 6 F 5 (1), Ph (2); R 0 ¼ C 6 H 2 Me 3 (a), tBu (b), Ph (c), C 6 F 5 (d), Me (e), H (f)] have been studied by performing quantum mechanical density functional theory and RI-MP2 calculations. Energy decomposition analyses based on the block-localized wavefunction method show that the nature of the interaction between R 3 B and PR 0 3 is strongly dependent on the BAP dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 138 publications
(219 reference statements)
0
6
0
Order By: Relevance
“…The starting point of our computational analysis of the six H 2 cleavage reactions is a comparison of the general features of the TSs, including the question whether the incoming H 2 has undergone any notable activation. The geometries of all TSs considered here have been published at various levels of theory; ,,,,,,,, now, we present a comparison on the basis of ωB97X-D/6-311G(d,p) results (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The starting point of our computational analysis of the six H 2 cleavage reactions is a comparison of the general features of the TSs, including the question whether the incoming H 2 has undergone any notable activation. The geometries of all TSs considered here have been published at various levels of theory; ,,,,,,,, now, we present a comparison on the basis of ωB97X-D/6-311G(d,p) results (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…However, experimental evidence of key intermediates and weakly interacting FLP encounter complexes in solution has been inconclusive, and recent investigations into reaction mechanisms have relied heavily on molecular simulation methods. Although the formation of a dative bond is “frustrated” in such systems, gas-phase calculations find interaction energies between the Lewis acid and base in the range of 5–15 kcal/mol, whereas molecular dynamics , modeling of encounter complexes in solution have revealed interactions along the potential of mean force on the order of k B T .…”
Section: Introductionmentioning
confidence: 99%
“…However, we were able to characterize an additional transition state in which H 2 adds to the external B–C bond involving the aromatic substituent bound to the boron center. Significantly, these transition states were found to be 72 and 46 kJ/mol higher in energy than the TS1 of boroles 1 and 2 , respectively . Furthermore, following the internal reaction coordinate toward products clearly showed that the characterized transition state leads to breakup of the B–C bond and subsequent formation of a borole with a B–H functionality and a molecule of benzene/pentafluorobenzene.…”
Section: Resultsmentioning
confidence: 91%